Direct calculation of the strong Goos-Hanchen effect of a Gaussian light beam due to the excitation of surface plasmon polaritons in the Otto configuration - Kim, Sangbum; Kim, Kihong (Journal of Optics (United Kingdom), 2019)
We theoretically study the influence of the surface plasmon excitation on the Goos-Hanchen lateral shift of a p-polarized Gaussian beam incident obliquely on a dielectric-metal bilayer in the Otto configuration. We find that the lateral shift depends sensitively on the thickness of the metal layer and the width of the incident beam, as well as on the incident angle. Near the incident angle at which surface plasmons are excited, the lateral shift changes from large negative values to large positive values as the thickness of the metal layer increases through a critical value. For wide incident beams, the maximal forward and backward lateral shifts can be as large as several hundred times of the wavelength. As the width of the incident Gaussian beam decreases, the magnitude of the lateral shift decreases rapidly, but the ratio of the width of the reflected beam to that of the incident beam, which measures the degree of the deformation of the reflected beam profile, increases. In all cases considered, we find that the reflected beam is split into two parts. We also find that the lateral shift of the transmitted beam is always positive and very weak.
Keywords: Direct calculation; Forward-and-backward; Gaussian light beams; Goos-Hanchen effect; Incident angles; Surface plasmon excitation; Surface plasmon polaritons; Transmitted beams; Gaussian beam; Goos-Hanchen effect; surface plasmon polariton